2010
DOI: 10.1097/mao.0b013e3181dbb37e
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Bone-Anchored Hearing Aid Application in Children

Abstract: Bilateral percutaneous BAHAs can be applied simultaneously from the age of 4 years, after a successful trial period with the BAHA Softband or other equivalent hearing aids. Bilateral BAHAs showed clear benefit in the vast majority. Outcomes of bilateral audiologic testing are needed in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 17 publications
1
32
0
2
Order By: Relevance
“…12, 24, 25 In 2001, Bosman et al evaluated sound localization and speech reception thresholds in noise and in quiet in 25 patients with bilateral BAHD. 26 They found that patients with bilateral BAHDs had significantly improved sound localization and improved speech recognition in quiet and in noise.…”
Section: Discussionmentioning
confidence: 99%
“…12, 24, 25 In 2001, Bosman et al evaluated sound localization and speech reception thresholds in noise and in quiet in 25 patients with bilateral BAHD. 26 They found that patients with bilateral BAHDs had significantly improved sound localization and improved speech recognition in quiet and in noise.…”
Section: Discussionmentioning
confidence: 99%
“…The BAHD has also been shown to be beneficial in children with bilateral and unilateral conductive or mixed hearing loss [5]. Subjective benefit was reported to be greater in children with bilateral BAHDs in terms of better sound localisation and speech recognition in noise [5][6][7].…”
Section: Indicationsmentioning
confidence: 97%
“…Christensen et al reviewed 23 children (age range [6][7][8][9][10][11][12][13][14][15][16][17][18][19] that had a BAHD for single sided deafness [8]. They assessed outcome using two questionnaires -Hearing in Noise Test (HINT) and Children's Home Inventory for Listening Difficulties (CHILD).…”
Section: Indicationsmentioning
confidence: 99%
“…Due to the small attenuation of vibrations in the skull, it has been argued that one BAHA can also stimulate the cochlea on the opposite side [10,20]. There have been studies, however, which report improved audiological outcomes and quality of life in children fitted with bilateral BAHAs [16,21,22], indicating that there may be a role for this intervention in some children. Fifty percent of our respondents have performed bilateral BAHAs in children.…”
Section: Discussionmentioning
confidence: 99%